DEDENG CERITA RAKYAT LANGKAT KAJIAN ANTROPOLOGIS - Syafna Elvira Utami; Nurelide Nurelide; Arianto Arianto (Balai Bahasa Sumatera Utara, 2022)
This study aims to describe the theme, setting, character, and cultural values. The object of research is a folk tale from the North Sumatra Province Language Center published in 2020. Data collection uses repeated reading and recording techniques. The data analysis technique is descriptive qualitative. The approach used is a literary anthropological approach. Research findings (1) The theme of Dedeng's story is